Preparation and physical properties of polypyrrole / zeolite composites - Mohd Tarmizi, Emma Ziezie; Hussein Baqiah, Hussein Abdullah; Talib, Zainal Abidin; Mohamed Kamari, Halimah (Elsevier, 2018)
Polypyrrole (PPy′)/zeolite composites were synthesized via chemical oxidation of pyrrole in the presence of zeolite. FeCl3 was used as an oxidant with the FeCl3-to-pyrrole molar ratio (MR) equal to 1. The zeolite contents were 0%, 5%, 10%, 15% and 20% of the total weight of PPy′. For comparison, pure PPy″ with FeCl3–pyrrole MR equal to 2 was also synthesized using the same method. The structural and physical properties of the samples were studied using X-rays diffraction (XRD), Fourier transform infrared spectroscopy, field emission electron scanning microscopy, thermogravimetric analysis, van Der Pauw technique and UV–VIS-NIR spectroscopy. The XRD of PPy′/zeolite (5%) revealed a presence of crystalline nature of zeolite in a spectrum of host amorphous PPy′. The XRD peaks increased, became stronger and shifted slightly to higher 2θ in PPy′/zeolite (10–20%) composites. Compared with PPy′, the composites were denser, more compact and had better thermal stability. The composites conductivity increased while their bandgap tended to reduce with increasing of zeolite. PPy′/zeolite (20%) composite had the highest conductivity value of 3.6 S cm−1 with an optical bandgap of 2.21 eV. The results showed that zeolite has been incorporated into PPy′ matrix and improved its physical properties.